Challenges in the Management of Higher Education in Uzbekistan and Prospective Solutions - Bakhonov Bekhruz Anvarovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the existing problems in managing the higher education system in Uzbekistan, their underlying causes, and possible future solutions. It examines the ongoing reforms in higher education, the introduction of modern management mechanisms, and the effective use of international experience. Special attention is given to improving the quality of training specialists, the application of digital technologies in the educational process, and the democratization of education management.